The Saccharomyces cerevisiae genome contains functional and nonfunctional copies of transposon Ty1. - Boeke, J D (1988)
Saccharomyces cerevisiae Ty elements are transposons closely related to retroviruses. The DNA sequence of a functional Ty element (TyH3) is presented. The long terminal repeat sequences are different, suggesting that TyH3 is a recombinant Ty element. A chromosomal Ty element near the LYS2 gene, Ty173, was found to be nonfunctional, even though it has no detectable insertions or deletions. The defect in Ty173 transposition is caused by a missense mutation giving rise to a Leu-to-Ile substitution in the TYB (pol) open reading frame. Several chromosomal Ty elements carry this lesion in their DNA, indicating that nonfunctional Ty elements are common in the yeast genome.